The Ability of Seasoning to Inhibit Contaminant Aspergillus spp. on Traditional Food Sardine Pedetan (Sardinella lemuru) - Singapurwa, Ni Made Ayu Suardani; Suprapta, Dewa Ngurah; Gunam, Ida Bagus Wayan; Wirya, I Gusti Ngurah Alit Susanta; Khalimi, Khamdan (Trends in Sciences, 2022)
Pedetan is processed food of seasoned sardine fish (Sardinella lemuru) which is preserved by drying. Isolation and identification of mold that contaminated the pedetan have been taken from 10 villages which are production centers in Jembrana Regency. Molds that can contaminate pedetan during storage, include Aspergillus flavus, Aspergillus aculeatus, Aspergillus niger, and Aspergillus tubingensis. In this research, the composition of the seasoning from the producer was used to inhibit the growth of contaminant fungi. The minimum antimicrobial inhibition test was carried out by the well diffusion method and the seasoning extract was tested for its inhibition on mold growth on potato dextrose agar (PDA) media. Mold colonies growth test and testing the effect of extracts on mold biomass were carried out in vitro with potato dextrose broth (PDB) media. The results showed that the composition of seasoning garlic, coriander, kaemfiera, galangal, ginger, vinegar, and salt can inhibit Aspergillus spp. Seasoning extract concentrations of 0.5 % (w/v) diameter of inhibitory zone minimum inhibitory concentration (MIC) are 0.8 and 1.2 mm for A. aculeatus and A. niger, by 1 mm for A. flavus and A. tubingensis, respectively. Seasoning extract at a concentration of 0.5 % (w/v) is also able to inhibit up to 100 % to the growth of the colony, conidia germination, conidia density, and biomass of A. flavus, A. aculeatus, A. niger, and A. tubingensis that contaminate the sardine fishes pedetan. HIGHLIGHTS Pedetan is processed food of seasoned sardine fish (Sardinella lemuru) which is preserved by drying Molds that can contaminate pedetan during storage, include Aspergillus flavus, Aspergillus aculeatus, Aspergillus niger, and Aspergillus tubingensis The composition of seasoning garlic, coriander, kaemfiera, galangal, ginger, vinegar, and salt can inhibit Aspergillus spp GRAPHICAL ABSTRACT